Pengaruh anti oksidan phenyl beta naphtylamine (PBN), dan variasi rss dengan SBR terhadap sifat fisika kompon talang karet - Siti Rochani; Asrilah Asrilah (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1998)
The aim of the research was to find some important characteristics of rubber gutter compound such as tensile strength, elongation at break, and constant deflection because of adding Phenyl Beta Naphtylamine on it. Rubber gutter compound was made from mixing of natural (RSS) and synthetic rubber (SBR) and some aditives such Zink Oxide, Stearic Acid, Napthenic Oil, HAF black, Phenyl Beta Naphtylamine, Mercapto Benz Thiazol Disulfide, Diphenyl Guanidine and Sulphur. Three compositions of RSS/SBR and Phenyl Beta Naphtylamine were used in the research, namely 40/60; 50/50; 60/40, and 1 : 1,5 ; 2 respectively. A statistical procedure was used to analyze the data of the physical characteristic of rubber gutter compound produced. The results were compared to the data of the physical characteristic of rubber gutter compound produced. The results were compared to the physical strength of rubber gutter available in the market. From the statistical analyses they denoted that the levels of Phenyl Beta Naphtylamine gave significant effects on elongation at break and constant deflection however there was no effect on tensile strength. The composition levels of RSS /SBR could produce compounds which were significant difference in the tensile strength, elongation at break and constant deflection. Compounds resulted from this research had better tensile strength and elongation compared to rubber gutter available in the market. INTISARI Penelitian ini bertujuan untuk mendapatkan karakteristik kompon talang karet terutama sifat-sifat penting seperti tegangan putus, perpanjangan putus dan pampat tetap, karena penambahan anti oksidan Phenyl Beta Naptylamine. Kompon talang karet dibuat dari campuran karet alam (RSS) dan karet sintetis (SBR) dengan enambahan bahan pembantu yaitu Zink Oksida, Asam Stearat, Naphtenic Oil, HAF black, Phenyl Beta Naphtylamine, Mercapto Benz Thiazol Disulphyte, Diphenyl Guanidine dan Sulfur. Campuran RSS dengan SBR di variasi dengan perbandingan 40/60; 50/50; dan 60/40, sedang Phenyl Beta Naphtylamine yang ditambahkan adalah 1; 1,5; dan 2 bagian. Kompon yang didapatkan, setelah diuji, hasilnya dianalisa dengan perhitungan statistik, serta dibandingkan dengan hasil uji talang karet dari pasaran. Dari hasil analisa statistik variasi Phenyl Beta Naphtylamine berpengaruh nyata pada sifat perpanjangan putus dan pampat tetap, sedangkan pada sifat tegangan putus tidak berbeda nyata. Variasi pencampuran RSS dengan SBR memberikan perbedaan yang nyata pada sifat fisis tegangan putus, perpanjangan putus dan pampat tetap. Dibandingkan dengan beberapa contoh yang diambil dari pasaran, kompon hasil penelitian mempunyai tegangan putus dan perpanjangan putus yang lebih baik.